1984
DOI: 10.1172/jci111635
|View full text |Cite
|
Sign up to set email alerts
|

Medullary collecting duct acidification. Effects of potassium, HCO3 concentration, and pCO2.

Abstract: Abstract. The medullary collecting duct (MCD) from renal outer medulla possesses significant HCO3 absorptive capacity. In vitro microperfusion studies have shown that HCO3 absorption in this segment is carbonic anhydrase dependent, affected by peritubular and luminal chloride concentrations, is independent of the presence of Na or the presence of Na transport, and is stimulated by mineralocorticoid hormone. The present in vitro microperfusion studies defined regulatory influences on MCD acidification as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 14 publications
(20 reference statements)
2
13
0
Order By: Relevance
“…The difference may be a result ofthe nominal presence of ambient CO2/ HCO in our studies that was removed to decrease any contribution to pHi by the Cl/HCO-exchanger (9). Jacobsen (25) has found that decreasing peritubular CO2 from 40 mmHg to 10-14 mmHg results in a 52% reduction in net transepithelial H' secretion. Thus, in our experiments JH may have been less than predicted from flux studies due to the nominal presence of CO2/HCO3.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The difference may be a result ofthe nominal presence of ambient CO2/ HCO in our studies that was removed to decrease any contribution to pHi by the Cl/HCO-exchanger (9). Jacobsen (25) has found that decreasing peritubular CO2 from 40 mmHg to 10-14 mmHg results in a 52% reduction in net transepithelial H' secretion. Thus, in our experiments JH may have been less than predicted from flux studies due to the nominal presence of CO2/HCO3.…”
Section: Discussionmentioning
confidence: 80%
“…Tubules were again bathed and luminally perfused in a Cl--free solution containing 25 Basolateral membrane Na+/H+ antiporter activity. Basolateral membrane Na+/H' antiporter activity was assessed as the Na'-dependent pHi recovery from an acid load.…”
Section: Chronic In Vivo Doca Administrationmentioning
confidence: 99%
“…The freed segment was then transferred to a thermostatically controlled lucite bath chamber on an inverted microscopic stage. The tubule was cannulated and perfused with concentric micropipettes as previously described (4,23,24). The inner perfusion pipette was advanced 50-100 Am into the tubule lumen and served as a bridge into the tubular lumen to measure transepithelial potential difference (PD, in millivolts).…”
Section: Methodsmentioning
confidence: 99%
“…These results were also averaged. The perfusate remained unchanged in all of these studies except for the assumed rapid equilibration of the bath and luminal Pco2 (25) (24,26,27 Effect ofchanging ambient Pco2. In experiments designed to simulate acute respiratory acid-base disorders, the bath Pco2 and pH were altered.…”
Section: Methodsmentioning
confidence: 99%
“…Several transport characteristics ofthe medullary collecting tubule make it an ideal segment to study the regulation of distal nephron acidification. These include no evidence for spontaneous net sodium or potassium transport (12); no evidence for bicarbonate secretion (8,13); independence of proton secretion from sodium transport or from the presence of sodium in luminal and peritubular fluids (7,14). With respect to active transport, the medullary collecting tubule thus appears to be involved exclusively in proton secretion.…”
Section: Introductionmentioning
confidence: 99%